2021
DOI: 10.2147/idr.s329183
|View full text |Cite
|
Sign up to set email alerts
|

Communicating COVID-19 Vaccine Safety: Knowledge and Attitude Among Residents of South East, Nigeria

Abstract: Background:The fight against the coronavirus disease (COVID-19), which has continued to threaten human existence globally, has led to the development of vaccines in order to control the rate of infection and death associated with the disease. Media messages on the COVID-19 vaccine are geared towards raising audience awareness and understanding of health risks, knowledge and attitudes about the vaccine safety. Objective: The study examined the knowledge and attitude towards COVID-19 vaccine safety media message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
3
12
0
1
Order By: Relevance
“…This is consistent with reports of similar studies that concluded that people who are more trusting in science and fear suffering from COVID-19 are in favour of getting the vaccination [2,14,21,25]. "People with a higher level of education are more inclined to believe in science because of their educational experience" [13,22,26].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with reports of similar studies that concluded that people who are more trusting in science and fear suffering from COVID-19 are in favour of getting the vaccination [2,14,21,25]. "People with a higher level of education are more inclined to believe in science because of their educational experience" [13,22,26].…”
Section: Discussionsupporting
confidence: 90%
“…"Achieving a high rate of vaccination is deemed a key to successfully combat the COVID-19 pandemic" [10]. "Efforts have been made in many countries to distribute vaccines against the virus to people at high risk of a severe or fatal course of the disease as well as to the rest of the population" [11][12][13]. "However, high vaccination rates are not solely the result of availability, effectiveness, and safety of vaccines, but also of people's willingness to get vaccinated" [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this, the doubt of the Filipinos on the side effects and its effectiveness is evident. In addition [50], [51] found that most of their respondents did not know the safety, efficacy, and side effects of the COVID-19 vaccine. Also, in the interview made by [41] about the reason for refusing the COVID-19 vaccine, their participants stated that they did not have enough information about the vaccine.…”
Section: Hesitancy Of the Respondents On Getting Vaccinated By The Co...mentioning
confidence: 99%
“…In time series forecasting, the ARIMA model is the most used method to handle linear information, whereas ANN S methods are adept at solving nonlinear problems, and the nonlinear autoregressive artificial neural network (NARANN) model has been demonstrated to have excellent mimic and prediction performances among ANNs models because this model has embedded memory function with the help of the tapped delay lines 45 . Therefore, the present study developed a novel mixture prediction model by considering the respective superiority of the EEMD, ARIMA, and NARANN in addressing time series forecasting issues to estimate the epidemiological trends of the COVID-19 prevalence and mortality in South Africa and Nigeria, the hardest-hit two countries with the outbreak in Africa 2 , 46 . Specifically, first, applying the EEMD technique to decompose the daily prevalence and mortality series into several Intrinsic Mode Functions (IMFs) subseries together with a residue subseries representing the trend of the data.…”
Section: Introductionmentioning
confidence: 99%